Dieter Müller–his legacies in Nordic tourism research - Viken A; Hall CM; Saarinen J (Taylor and Francis Group, 2026)
In November 2025, Professor Dieter Müller of the University of Umeå suddenly passed away while returning from a work meeting in Norway. His unexpected death sent shockwaves through the Nordic tourism and geography communities to which he has long been a significant contributor. This paper celebrates his life and work, which linked theory development with empirical studies and his contributions to Nordic tourism research. Three main themes are identified: second home tourism, Sámi tourism, and Arctic tourism geography. The commonalities of the three areas are that Dieter saw tourism as a dynamic and modernising industrial and social field, significant for wellbeing, and important to regional development and the societal development of the Arctic region. In addition, there is an awareness of tourism’s ethnopolitical significance and, more recently, geopolitical significance, viewing tourism as both a changing force in society and as a product of societal changes.
Keywords: Second home tourism; Sámitourism; Arctic tourism; artification; tourism geography